Silicate nanoparticles by bioleaching of glass and modification of the glass surface - Kulkarni, Sneha; Syed, Asad; Singh, Sanjay; Gaikwad, Anil; Patil, Kashinath; Vijayamohanan, K.; Ahmad, Absar; Ogale, Satishchandra (Journal of Non-Crystalline Solids, 2008)
Bioleaching is examined as a low temperature (50 degrees C) soft chemical approach to nanosynthesis and surface processing. We demonstrate that fungus based bioleaching of borosilicate glass enables synthesis of nearly monodispersed ultrafine (similar to 5 +/- 0.5 nm) silicate nanoparticles. Using various techniques such as X-ray diffraction, X-ray photoelectron spectroscopy and FTIR we compare the constitution and composition of the nanoparticles with that of the parent glass, and establish the basic similarities between the two. The bioleaching process is shown to enhance the non-bridging oxygen component and correspondingly influence the Si-O-Si network. The root mean square roughness of glass surface is seen to increase from 1.27 nm for bare glass to 2.52 nm for 15 h fungal processed case, this increase being equivalent to that for glass annealed at 500 degrees C. (c) 2008 Elsevier B.V. All rights reserved.
Keywords: Bioglass; Biomaterials; borosilicates; narroparticles

Strong photo-response in a flip-chip nanowire p-Cu2O/n-ZnO junction - Deo, Meenal S.; Mujawar, Sarfraj; Game, Onkar S.; Yengantiwar, Ashish; Banpurkar, Arun G.; Kulkarni, Sneha; Jog, Jyoti Prakash; Ogale, Satishchandra B. (Nanoscale, 2011)
Cu2O nanoneedles are synthesized on a copper substrate by a simple anodization and reducing ambient annealing protocol. ZnO nanorods are grown on ITO coated glass by a low temperature chemical route. The electronic and photo-response properties of the p-Cu2O/n-ZnO flip-chip heterojunction are then studied and analyzed. We show that the I-V characteristic is rectifying and the junction exhibits a good photoresponse (similar to 120% under 1 V reverse bias) under AM 1.5 (1 Sun) illumination. This nano-heterojunction photo-response is far stronger as compared to that of a pulsed laser deposited thin film p-Cu2O/n-ZnO heterojunction, which can be attributed to higher junction area in the former case.